المجتمعات المهنية للتعلم ودورها في تحسين جودة الأدإ المدرسي لدى مديري المدارس والمديرين المساعدين في سلطنة عمان - Fatema Mohammed Salim Al-Salehi
This study aimed to reveal the importance of professional learning communities and their role in improving the quality of school performance among school principals and assistant principals in the Sultanate of Oman. This study intended to identify a possible relationship between applying the dimensions of professional learning communities and improving the school performance in terms of administration, teaching, and learning. Statistical differences in the dimensions of professional learning coininunities and the quality of school perfonnance by school principals and assistant principals were examined, based on their demographic variables, namely gender, district, qualification, level of education, job title, and years of experience. To achieve the objectives of the study, the descriptive analytical approach is used. Theoretical literature about the study's area was perused, while the data was collected using a questionnaire consisting of 76 iteins that represented four constructs. The questionnaire was distributed to 180 school principals and 224 assistant principals in the provinces of North Batinah and South Batinah. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to verify the construct validity and reliability of the constructs. Independent samples t-test and one-way ANOVA were performed to examine any statistical differences among the respondent's demographic variables. Additionally, content analysis was done on the semi-structured interviews conducted with ten key participants. Most importantly, the analyses suggest that the level of practices of professional learning communities and the improvement of the quality of school performance among school principals and assistant principals were high. The relationship between the application of the dimensions of professional learning communities and the improvement of the quality of school performance was also shown to be relevant and important. There was a direct impact on the dimensions of professional learning communities on the improvement of the quality of school performance. These findings were demonstrated through their practices and the analysis of the content of the development plans of the schools. The results of the affirmative coefficient analysis indicated the indicators' reliability and suitability for the four dimensions of the study. The study also showed that there were no statistically significant differences at the alpha level of 0.05 based on the respondents' gender, province, education, and job title in the four dimensions (management practices, education practices, learning practices, and improvement of performance quality). However, this study found that at the level of alpha of 0.05, there were statistically significant differences in the management practices based on the respondents' qualification. There were also differences found in the teaching and learning practices based on the respondents' gender, as well as differences between the teaching practices were based on the respondents' experience. This study presented suggestions and recommendations, the most important of which is establishment of an electronic learning platform for the professional learning communities under the supervision of the Specialized Centre for Vocational Training of Teachers (Ministry of Education). The aim of this platform is threefold, i.e. to exchanging strategies on improvement in the fields of school performance, to provide consultation regarding practices and experiences, and to facilitate coinmunication between trainers and trainees in an effective learning environment.